2014
DOI: 10.1051/0004-6361/201424237
|View full text |Cite
|
Sign up to set email alerts
|

A semianalytical light curve model and its application to type IIP supernovae

Abstract: The aim of this work is to present a semianalytical light curve model code that can be used for estimating physical properties of core collapse supernovae (SNe) in a quick and efficient way. To verify our code we fit light curves of Type II SNe and compare our best parameter estimates to those from hydrodynamical calculations. For this analysis, we use quasi-bolometric light curves of five different Type IIP SNe. In each case, we obtain appropriate results for initial pre-supernova parameters. We conclude that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(93 citation statements)
references
References 35 publications
(83 reference statements)
2
89
0
2
Order By: Relevance
“…Falk & Arnett 1977;Utrobin 2007;Bersten et al 2011;Pumo & Zampieri 2011). The model has been implemented by Nagy et al (2014) and Bose et al (2015b) for several type II SNe to estimate explosion parameters and are found to be fairly consistent with results from hydrodynamical models. Description of model formulation and algorithm is presented in Bose et al (2015b) and references therein.…”
Section: Light Curve Modellingmentioning
confidence: 65%
See 2 more Smart Citations
“…Falk & Arnett 1977;Utrobin 2007;Bersten et al 2011;Pumo & Zampieri 2011). The model has been implemented by Nagy et al (2014) and Bose et al (2015b) for several type II SNe to estimate explosion parameters and are found to be fairly consistent with results from hydrodynamical models. Description of model formulation and algorithm is presented in Bose et al (2015b) and references therein.…”
Section: Light Curve Modellingmentioning
confidence: 65%
“…Description of model formulation and algorithm is presented in Bose et al (2015b) and references therein. The temporal component of temperature evolution in a comoving frame of expansion is given (Arnett & Fu 1989;Nagy et al 2014) as,…”
Section: Light Curve Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we generalize the semi-analytic LC model presented by Nagy et al (2014), which assumes a homologously expanding and spherically symmetric SN ejecta. The density structure of the ejecta is assumed to include an inner part with flat (constant) density extending to a dimensionless radius x 0 , and an outer part where the density decreases as an exponential or a power-law function.…”
Section: Two-component Light-curve Modelmentioning
confidence: 99%
“…In this paper we use a semi-analytic light-curve model, which was originally presented by Arnett & Fu (1989) and later extended by Popov (1993), Blinnikov & Popov (1993), and Nagy et al (2014), to describe the double-peaked light curves of several types of CCSNe. This model is able to produce a wide variety of SN light curves depending on the choice of the initial parameters, such as the ejected mass (M ej ), the initial radius of the progenitor (R 0 ), the total explosion energy (E tot ), and the mass of the synthesized 56 Ni (M Ni ), which directly determines the emitted flux at later phases.…”
Section: Introductionmentioning
confidence: 99%